The heights : anatomy of a skyscraper - Ascher, Kate. (New York : Penguin Press, 2011)
A graphic tour through the inner workings of modern skyscrapers explains how they operate and how sophisticated networks of technologies and utilities are possible within their complex structures.
History -- Building it. Design ; Foundations ; Structure ; The skin ; Construction -- Living in it. Elevators ; Power, air, and water ; Communications -- Supporting it. Life safety ; Maintenance ; Sustainability -- Dreaming it. The future.
Includes index.
boek